PENGAWASAN PARTISIPATIF SEBAGAI WUJUD PELAYANAN PUBLIK DEMOKRATIS DALAM PENGAWASAN TAHAPAN DAN NON-TAHAPAN PEMILU OLEH BAWASLU - Kamaludin; Muhammad Aini (JOURNAL OF LAW AND NATION, 2026)
Participatory supervision constitutes one of the strategic approaches developed by the Election Supervisory Agency (Bawaslu) to strengthen public involvement in safeguarding the integrity of electoral processes. Thus far, participatory supervision has generally been understood as an instrument for electoral oversight aimed at preventing violations and expanding the scope of supervision. However, from the perspective of public service, participatory supervision also reflects a form of democratic public service provided by Bawaslu to facilitate citizens' constitutional rights to participate in democratic governance. This study aims to analyze the position of participatory supervision as a democratic public service implemented by Bawaslu, examine its implementation during electoral and non-electoral stages, and identify efforts to strengthen participatory supervision in supporting electoral integrity. This research employs a normative legal method using statutory and conceptual approaches. The study reveals that participatory supervision fulfills the essential elements of public service because it is organized by a public institution, directed toward citizens, and designed to provide access, information, education, participation mechanisms, and reporting channels related to electoral oversight. Furthermore, participatory supervision embodies the principles of democratic public service by promoting citizen engagement, transparency, accountability, and collaborative governance in electoral administration. Its implementation is carried out through various programs, including electoral supervision socialization, the Participatory Supervision Village Program, the School of Participatory Supervisory Cadres, partnerships with educational institutions and civil society organizations, as well as public reporting mechanisms. Nevertheless, several challenges remain, including limited public awareness, uneven electoral literacy, institutional capacity constraints, and the sustainability of participatory programs. Therefore, strengthening regulatory frameworks, institutional capacity, digital innovation, and collaborative engagement is necessary to optimize participatory supervision as a democratic public service and to support the realization of elections that are both democratic and accountable.